Totally random questions. Volume 2 : 101 odd and awesome Q&As - Bellows, Melina Gerosa (Random House Children's Books, 2022)
Contains a list of 101 true-or-false and multiple-choice trivia questions, followed by explanatory answers, color photographs, and additional information. Covers topics such as animals, science, sports, food, and weather among other subjects.